Bacterial Disease Diagnostics - Sabarinath, T.; Agarwal, R. K.; Chaudhuri, Pallab (Indian Farming, 2015)
The IVRI posseses and has the best of diagnostics facilities as far as bacterial diseases are concerned. The conventional bacterial disease diagnosis in India started with the establishment of Division of Bacteriology and Mycology in 1975 at IVRI, Izatnagar. The Division of Biological Products is currently producing antigens related to various bacterial diseases prevalent in the livestock, on a commercial scale and distributing these diagnostics to various veterinary institutions and the state government diagnostic laboratories across the country.